Incidence of serious infections in patients with ANCA-associated vasculitis receiving immunosuppressive therapy: A systematic review and meta-analysis - Vassilopoulos, Athanasios; Vassilopoulos, Stephanos; Kalligeros, Markos; Shehadeh, Fadi; Mylonakis, Eleftherios (Frontiers in Medicine, 2023)
Introduction Rituximab and azathioprine are used to induce or maintain remission in patients with ANCA-associated vasculitis (AAV). We evaluated the incidence of serious infections and infection-related deaths in patients with AAV treated with rituximab and azathioprine, during the maintenance of remission period. Methods We searched PubMed and EMBASE for randomized clinical trials (RCTs) and observational studies evaluating immunosuppressive agents in patients with AAV. We defined serious or severe infections according to the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. The study was registered on PROSPERO (CRD42022366269). Results From 1,265 abstracts, we identified 21 studies (7 RCTs and 14 observational), with relevant data. We included data from 1,284 and 2,938 individuals for assessment in our primary and secondary outcomes, respectively. The overall cumulative incidence of serious infections was 15.99% (CI 95%: 6.95–27.53%) during the total follow-up period (induction and maintenance) and 7.62% (CI 95%: 4.43–11.43%) during the maintenance period. Additionally, we found a 0.49% overall case fatality rate (CI 95%: 0.02–1.37%) and a 0.09% infection-related mortality rate (CI 95%: 0.00–0.51%) during maintenance treatment. Notably, we found a 14.61% (CI 95%: 10.19–19.61%) cumulative incidence of serious infections among patients who received rituximab and a 5.93% (CI 95%: 1.19–13.26%) cumulative incidence of serious infections among patients who received azathioprine during maintenance. Moreover, the cumulative incidence of serious infections during the total follow-up period (induction and maintenance) was 20.81% (CI 95%:4.56–43.70%) for the combination of cyclophosphamide and azathioprine and 14.12% (CI 95%: 5.20–26.00%) for rituximab. Discussion The cumulative incidence of serious infections during total follow-up and maintenance was within expected limits, while fatal infections during maintenance treatment were uncommon. Additionally, treatment with rituximab for both induction and maintenance did not exceed the anticipated by previous studies incidence of serious infections. Clinical practice and long-term follow up data are needed to corroborate these findings. Systematic review registration Identifier: PROSPERO (CRD42022366269).